Perceived Hospital Responsiveness and Patient Satisfaction at Undata General Hospital Palu: A Cross-Sectional Study - Muhammad Syukran; Maudiah Nabila Putri; Munir Salham; Sudirman Sudirman; Mohamad Andri; Intan Fitrah Andini (Poltekkes Kemenkes Palu, 2026)
Background: Patient satisfaction is an important indicator of hospital service quality, but hospitals often need evidence on which service-quality dimensions are most closely associated with patient evaluations. This study examined the association between perceived hospital responsiveness, measured using SERVQUAL-derived responsiveness items, and patient satisfaction at Undata General Hospital Palu. Methods: This quantitative cross-sectional study analyzed 96 valid patient survey responses collected at Undata General Hospital Palu, Central Sulawesi, Indonesia, from December 2025 to January 2026. Respondents were outpatient JKN (National Health Insurance) users selected using accidental sampling. Eligible respondents were patients who had a minimum of three visits to the hospital. Responsiveness was measured using four Likert-scale items, and patient satisfaction was measured using ten Likert-scale items. Composite scores were categorized using a 75% threshold. Descriptive statistics, cross-tabulation, Fisher’s exact test, crude odds ratio estimation, and correlation analysis were performed. Although formal ethical approval was not obtained, the study was conducted with consideration of ethical principles, including voluntary participation, informed consent, and confidentiality Results: Overall, 59.4% of respondents perceived hospital responsiveness as good, whereas only 26.0% were categorized as satisfied. Satisfaction was reported by 40.4% of respondents in the good-responsiveness group and 5.1% in the poor-responsiveness group. Good perceived responsiveness was associated with higher odds of satisfaction (crude OR = 12.51; 95% CI: 2.74–57.11; p < 0.001), although the wide confidence interval indicates limited precision. Score-based analysis also showed positive correlations between responsiveness and satisfaction using Pearson correlation (r = 0.681; p < 0.001) and Spearman correlation (ρ = 0.600; p < 0.001) Conclusion: Perceived hospital responsiveness was significantly associated with patient satisfaction in this cross-sectional study. However, the low overall satisfaction rate despite relatively favorable responsiveness ratings suggests that responsiveness alone does not fully explain patient satisfaction. Broader assessment of other service-quality dimensions is needed to guide patient-centred hospital quality improvement.